Hierarchical multi-shell 66-nuclei silver nanoclusters trapping subvalent Ag6 kernels. Issue 69 (9th August 2019) - Wang, Zhi; Yang, Feng-Lei; Yang, Yang; Liu, Qing-Yun; Sun, Di
Abstract : Three novel hierarchical multi-shell 66-nuclei silver nanoclusters trapping ultrasmall Ag6 4+ units were realized by the combination of mild reductive DMF and multiple anions. Abstract : Hierarchical nano structures are hard to fabircate. Here, we present three novel hierarchical multi-shell 66-nuclei silver nanoclusters, trapping ultrasmall Ag6 4+ nano-fragments by nine MoO4 2− ions. This Ag6 @(MoO4 )9 core is further wrapped by an outer Ag60 shell. The Ag6 kernel evolves from reduction involving DMF solvent. Carboxylate ligands are very important in the modulation of the polygon patterns on the Ag60 shell.